Temperature-dependent hysteresis model for soft magnetic materials. Issue 5 (30th July 2019) - Longhitano, Maria Roberta; Sixdenier, Fabien; Scorretti, Riccardo; Krähenbühl, Laurent; Geuzaine, Christophe
Abstract : Purpose: To understand the behavior of the magnetization processes in ferromagnetic materials in function of temperature, a temperature-dependent hysteresis model is necessary. This study aims to investigate how temperature can be accounted for in the energy-based hysteresis model, via an appropriate parameter identification and interpolation procedure. Design/methodology/approach: The hysteresis model used for simulating the material response is energy-consistent and relies on thermodynamic principles. The material parameters have been identified by unidirectional alternating measurements, and the model has been tested for both simple and complex excitation waveforms. Measurements and simulations have been performed on a soft ferrite toroidal sample characterized in a wide temperature range. Findings: The analysis shows that the model is able to represent accurately arbitrary excitation waveforms in function of temperature. The identification method used to determine the model parameters has proven its robustness: starting from simple excitation waveforms, the complex ones can be simulated precisely. Research limitations/implications: As parameters vary depending on temperature, a new parameter variation law in function of temperature has been proposed. Practical implications: A complete static hysteresis model able to take the temperature into account is now available. The identification is quite simple and requires very few measurements at different temperatures. Originality/value: The results suggest that it is possible to predict magnetization curves within the measured range, starting from a reduced set of measured data.